2021
DOI: 10.1371/journal.pgen.1008943
|View full text |Cite
|
Sign up to set email alerts
|

A forward genetic screen identifies Dolk as a regulator of startle magnitude through the potassium channel subunit Kv1.1

Abstract: The acoustic startle response is an evolutionarily conserved avoidance behavior. Disruptions in startle behavior, particularly startle magnitude, are a hallmark of several human neurological disorders. While the neural circuitry underlying startle behavior has been studied extensively, the repertoire of genes and genetic pathways that regulate this locomotor behavior has not been explored using an unbiased genetic approach. To identify such genes, we took advantage of the stereotypic startle behavior in zebraf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 96 publications
6
8
0
Order By: Relevance
“…We tested an acoustic startle protocol on 5 dpf larvae for 10 minutes by introducing vibration pulses of 440Hz in light (Figure 3A) and calculated the total distance travelled at the end of every 1 minute. The kcna1a −/− larvae moved significantly longer distances during the second and third pulses compared to WTs, consistent with an abnormal response to acoustic startle (Figure 3B) and a recent study (29). We also performed a protocol of light-dark flashes on 5 dpf larvae for a duration of 90 seconds (Figure 3C) and measured the total distance travelled at the end of every 3 seconds.…”
Section: Resultssupporting
confidence: 88%
“…We tested an acoustic startle protocol on 5 dpf larvae for 10 minutes by introducing vibration pulses of 440Hz in light (Figure 3A) and calculated the total distance travelled at the end of every 1 minute. The kcna1a −/− larvae moved significantly longer distances during the second and third pulses compared to WTs, consistent with an abnormal response to acoustic startle (Figure 3B) and a recent study (29). We also performed a protocol of light-dark flashes on 5 dpf larvae for a duration of 90 seconds (Figure 3C) and measured the total distance travelled at the end of every 3 seconds.…”
Section: Resultssupporting
confidence: 88%
“…Mutations in both hip14 and kcna1a strongly upregulate activity in the spiral fiber neuron clusters as well as in V2a neurons (S2D). Dysfunction of V2a neurons within the spinal cord was previously proposed as a potential mechanism underlying the kinematic deficits observed in kcna1a mutants 31 , and we now hypothesize that hyperactivation of V2a neurons within the hindbrain could contribute to the habituation deficits observed in kcna1a mutants. Spiral fibers also constitute an attractive locus for Kv1.1’s activity in regulating learning.…”
Section: Discussionsupporting
confidence: 55%
“…We found a remarkably specific and unique pattern of activity induced by the loss of kcna1a . In particular, two populations known to express Kv1.1 24,31 and involved in the execution of the escape response were found to be hyperactive: spiral fiber neurons and RoM3 excitatory reticulospinal (V2a) neurons (Figure 3G-I). We previously showed that Kv1.1 requires Hip14 for proper synaptic localization and hence likely acts downstream of Hip14 to regulate habituation learning.…”
Section: Resultsmentioning
confidence: 99%
“…Acoustically-Evoked Behavior: After acclimating to testing conditions on a light box for 45min, healthy fish were placed in individual wells of a custom plexiglass testing arena, either 9mm diameter wells in a 36-well arena or 9mm x 9mm square wells of a 16-well arena, illuminated from below with an IR array (CM-IR200-850, CMVision), attached to a vibrational exciter (4810, Brüel & Kjaer) that administers acoustic stimuli, as previously described (Jain et al, 2018;Meserve et al, 2021). Acoustic stimuli were 2ms tones (1000 Hz), varying intensity as needed for each assay.…”
Section: Behavioral Testing and Analysismentioning
confidence: 99%